The Chloroplast Envelope Protease FTSH11 – Interaction With CPN60 and Identification of Potential Substrates - Adam, Zach; Aviv-Sharon, Elinor; Keren-Paz, Alona; Naveh, Leah; Rozenberg, Mor; Savidor, Alon; Chen, Junping (Frontiers in Plant Science, 2019)
FTSH proteases are membrane-bound, ATP-dependent metalloproteases found in bacteria, mitochondria and chloroplasts. The product of one of the 12 genes encoding FTSH proteases in Arabidopsis, FTSH11, has been previously shown to be essential for acquired thermotolerance. However, the substrates of this protease, as well as the mechanism linking it to thermotolerance are largely unknown. To get insight into these, the FTSH11 knockout mutant was complemented with proteolytically-active or inactive variants of this protease, tagged with HA-tag, under the control of the native promoter. Using these plants in thermotolerance assay demonstrated that the proteolytic activity, and not only the ATPase one, is essential for conferring thermotolerance. Immunoblot analyses of leaf extracts, isolated organelles and sub-fractionated chloroplast membranes localized FTSH11 mostly to chloroplast envelopes. Affinity purification followed by mass spectrometry analysis revealed interaction between FTSH11 and different components of the CPN60 chaperonin. In affinity enrichment assays, CPN60s as well as a number of envelope, stroma and thylakoid proteins were found associated with proteolytically-inactive FTSH11. Comparative proteomic analysis of WT and knockout plants, grown at 20oC or exposed to 30oC for 6 hrs, revealed a plethora of upregulated chloroplast proteins in the knockout, some of them might be candidate substrates. Among these stood out TIC40, which was stabilized in the knockout line after recovery from heat stress, and three proteins that were found trapped in the affinity enrichment assay: the nucleotide antiporter PAPST2, the fatty acid binding protein FAP1 and the chaperone HSP70. The consistent behavior of these four proteins in different assays suggest that they are potential FTSH11 substrates.